Patient's Right to Consent to Medical Procedures from the Perspective of Health Law, Bioethics, and Human Rights - Ni Putu Parvathi Priyadarshini; I Gusti Ayu Putri Kartika (Dinasti Research, 2025)
The patient's right to consent to medical procedures is a vital element in the relationship between patients and healthcare providers, connected to health law, bioethics, and human rights, all focusing on the protection of patient autonomy. This study analyzes the patient's right to consent from the perspectives of health law, bioethics, and human rights, and identifies challenges in its implementation in Indonesia. A normative method is employed with legislative, conceptual, and comparative approaches. Data is gathered by analyzing national regulations, bioethical principles, and literature on human rights. Descriptive-analytical analysis was used to explore the synergy between these three perspectives in medical consent implementation. Findings reveal that the patient's right to consent is regulated by Law No. 17 of 2023 and other relevant regulations. Bioethics stresses respecting patient autonomy, while human rights ensure access to information and the freedom to consent. Challenges include paternalistic cultural attitudes, low public awareness, and inadequate healthcare facilities. Recommendations include strengthening regulations, providing bioethics training for healthcare professionals, and educating the public to safeguard patient rights in medical procedures in accordance with health law, bioethics, and human rights.